Long-Term Failure After Restorative Proctocolectomy for Ulcerative Colitis - Hagit Tulchinsky; P R Hawley; John Nicholls (2003)
In Brief Objective To establish the incidence and causes of late failure in patients undergoing restorative proctocolectomy for a preoperative diagnosis of ulcerative colitis was the objective of this investigation. Summary Background Data Restorative proctocolectomy is the elective surgical procedure of choice for ulcerative colitis. Most patients have a satisfactory outcome but failures occur. The reasons and rates of early failure are well documented, but there is little information on long-term failure. Methods A series of 634 patients (298 females, 336 males) underwent restorative proctocolectomy for inflammatory bowel disease between 1976-1997, with a mean follow-up of 85 ± 58 months. Failure was defined as removal of the pouch or the need for an indefinite ileostomy. It was divided into early and late, occurring within 1 year or more than 1 year postoperatively. Results There were 3 (0.5%) postoperative deaths, leaving 631 patients for analysis. Of these, 23 subsequently died (disseminated large bowel cancer, 12; unrelated causes, 9; related causes, 2). There were 61 (9.7%) failures (15 early [25%], 46 late [75%]) due to pelvic sepsis (32 [52%]: 7 early, 25 late), poor function (18 [30%]: 2 early, 16 late), pouchitis (7 [11%]: 2 early, 5 late) and miscellaneous (4, all early). A final diagnosis of Crohn's disease, type of reservoir (J,S), female gender, postoperative pelvic sepsis and a one-stage procedure were significantly associated with failure. Failure rate rose with time of follow-up from 9% at 5 years to 13% at 10 years. Conclusions Pelvic sepsis and poor function were the main reasons for later failure. Failure rates should be reported based on the duration of follow-up. Over 22 years, 634 patients underwent restorative proctocolectomy for inflammatory bowel disease. At a mean follow-up of 85 months, overall failure was 9.7% with pelvic sepsis and poor function being the commonest reasons. Failure was cumulative with time, with a prevalence of 9% at 5 years rising to 13% at 10 years.